2014
DOI: 10.1371/journal.pone.0104419
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Inverse PCR for Exploration of Ligated Breakpoints (GIPFEL), a New Method to Detect Translocations in Leukemia

Abstract: Here we present a novel method “Genomic inverse PCR for exploration of ligated breakpoints” (GIPFEL) that allows the sensitive detection of recurrent chromosomal translocations. This technique utilizes limited amounts of DNA as starting material and relies on PCR based quantification of unique DNA sequences that are created by circular ligation of restricted genomic DNA from translocation bearing cells. Because the complete potential breakpoint region is interrogated, a prior knowledge of the individual, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…To date, we have conducted the only study identifying ETV6-RUNX1 + cells via DNA quantification [7]. We used the novel GIPFEL technique [50], allowing for the indirect identification of chromosomal translocations at the DNA level. In this study, we identified 5% of healthy newborns to be ETV6-RUNX1 + .…”
Section: Etv6-runx1mentioning
confidence: 99%
“…To date, we have conducted the only study identifying ETV6-RUNX1 + cells via DNA quantification [7]. We used the novel GIPFEL technique [50], allowing for the indirect identification of chromosomal translocations at the DNA level. In this study, we identified 5% of healthy newborns to be ETV6-RUNX1 + .…”
Section: Etv6-runx1mentioning
confidence: 99%
“…It has been shown to be associated with monocytic AML phenotypes and proven to be of functional relevance for leukemogenesis. [13][14][15] It is interesting to note that RKIP loss has also been observed in a variety of solid cancers and has been described as a bona fide…”
Section: Authorshipmentioning
confidence: 99%
“…Only DNA-based techniques can differentiate between breakpoints that are specific for each individual patient and localized in intronic regions. (B-E) The workflow of cord blood screening using a modified GIPFEL technique 15 is presented. (B) CD19 1 B cells were enriched from newborn cord blood.…”
mentioning
confidence: 99%
See 2 more Smart Citations